The use of cryopreserved platelets in the treatment of polytraumatic patients and patients with massive bleeding - Bohonek, Milos; Kutac, Dominik; Landova, Ludmila; Koranova, Michaela; Sladkova, Eliska; Staskova, Eva; Voldrich, Martin; Tyll, Tomas (Transfusion, 2019)
BACKGROUND: The short shelf-life of fresh platelets limits their efficient inventory management and availability during a massive transfusion protocol. Risk of insufficient availability can be mitigated by building an inventory of cryopreserved platelets (CPs). METHODS: A comparative study of fresh apheresis platelets (FAPs) and CPs was performed. Type-O CPs were processed with DMSO frozen at -80°C and reconstituted in thawed AB plasma. All patients enrolled in the study had the following parameters evaluated on admission: vital signs (body temperature, heart rate, mean arterial pressure), blood count, prothrombin time, activated partial thromboplastin time, fibrinogen level, and, in trauma patients, international severity score. Several outcomes were evaluated: 30-day survival, adverse events, quantity of administered blood products, fibrinogen concentrate and thromboxane (TXA), and laboratory parameters after transfusion (blood count, prothrombin time, activated partial thromboplastin time, fibrinogen level). RESULTS: Twenty-five (25) patients in the study group received transfusions totaling 81 units of CPs. Twenty-one (21) patients in the control group received a total of 67 units of FAPs. There were no significant differences in patient characteristics (p > 0.05) between groups. Both groups were comparable in clinical outcomes (30-day survival, administered blood products, fibrinogen concentrate, TXA, and adverse events). Among posttransfusion laboratory parameters, platelet count was higher in the group transfused with FAPs (97.0 ×109 /L) than in the group transfused with CPs (41.5 ×109 /L), p = 0.02025. Other parameters were comparable in both groups. CONCLUSION: The study suggests that CPs are tolerable and a feasible alternative to FAPs. However, larger randomized studies are needed to draw definitive conclusions.
Keywords: fibrinogen; dospělí; polytrauma; Cryopreservation; Female; transfuze trombocytů; Adult; ženské pohlaví; trombocyty; Multiple Trauma; krvácení; lidé; Platelet Transfusion; Aged, 80 and over; trombocytaferéza; Plateletpheresis; kryoprezervace; Blood Platelets; Male; Prothrombin Time; Aged; protrombinový čas; Hemorrhage; Partial Thromboplastin Time; parciální tromboplastinový čas; lidé středního věku; Fibrinogen; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans